2021
DOI: 10.1021/acsomega.1c01289
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Novel Anticancer Small-Molecule RNA m6A Demethylase ALKBH5 Inhibitors

Abstract: The RNA 6-N-methyladenosine (m6A) demethylase ALKBH5 has been shown to be oncogenic in several cancer types, including leukemia and glioblastoma. We present here the target-tailored development and first evaluation of the antiproliferative effects of new ALKBH5 inhibitors. Two compounds, 2-[(1-hydroxy-2-oxo-2-phenylethyl)­sulfanyl]­acetic acid (3) and 4-{[(furan-2-yl)­methyl]­amino}-1,2-diazinane-3,6-dione (6), with IC50 values of 0.84 μM and 1.79 μM, respectively, were identified in high-throughput virtual sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…Considering the multileveled entanglement of epitranscriptomics with IHD pathophysiology, that is even suggested as a driver of some crucial steps of its pathogenesis [ 75 ], these modifications could also provide a novel source of therapeutic drug targets for IHD. Indeed, small molecule ligands for METTL3 writer complex [ 116 ], FTO [ 170 ], and ALKBH5 [ 171 ] erasers have already been described by the members of the IHD-EPITRAN Consortium. Remarkably, just recently, a potent METTL3 inhibitor has also been reported with leukemia-repressing effects in vivo in mice, providing simultaneously an enchanting proof-of-principle and a seminal endeavor to thrust the door ajar into the yet uncharted realm of epitranscriptomics-based pharmacology in vivo—ultimately shifting eyes also increasingly towards the clinic [ 172 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the multileveled entanglement of epitranscriptomics with IHD pathophysiology, that is even suggested as a driver of some crucial steps of its pathogenesis [ 75 ], these modifications could also provide a novel source of therapeutic drug targets for IHD. Indeed, small molecule ligands for METTL3 writer complex [ 116 ], FTO [ 170 ], and ALKBH5 [ 171 ] erasers have already been described by the members of the IHD-EPITRAN Consortium. Remarkably, just recently, a potent METTL3 inhibitor has also been reported with leukemia-repressing effects in vivo in mice, providing simultaneously an enchanting proof-of-principle and a seminal endeavor to thrust the door ajar into the yet uncharted realm of epitranscriptomics-based pharmacology in vivo—ultimately shifting eyes also increasingly towards the clinic [ 172 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study also identified that a new FTO inhibitor, FTO-04, could disrupt glioblastoma stem cells self-renewal, which indicates that FTO-04 may act as a potential treatment for glioblastoma (105). For the other eraser, ALKBH5, there is only one study that reported that two compounds, compound 3 (2-[(1hydroxy-2-oxo-2-phenylethyl)sulfanyl]acetic acid) and compound 6 (4-{[(furan-2-yl)methyl]amino}-1,2-diazinane-3,6-dione), identified as ALKBH5 inhibitors, could suppress the growth of three leukemia cell lines (106). Noticeably, inhibitors of FTO and ALKBH5 are effective in certain subtypes of AMLs and some solid tumors where FTO or ALKBH5 is overexpressed and promotes tumorigenesis, suggesting that these inhibitors may have promising and broad roles in cancer therapy.…”
Section: Progress In the Application Of Small Molecules Targeting M6a Regulatorsmentioning
confidence: 99%
“…Thus, targeting RNA m6A demethylases, such as ALKBH5 which is overexpressed in breast cancer and promotes stem cell maintenance [ 247 , 248 , 249 , 250 ] might restore MAGI3 full-length expression, hampering YAP1 signaling and promoting the PTEN tumor suppressor pathway. In this context, some inhibitors of ALKBH5 are under development and proved to efficiently exert antiproliferative activity in a cancer-cell-type-selective manner [ 251 ]. As far as MAGI1 is wild-type, its accumulation could be raised by Cox2 inhibitors leading to increased PTEN stability and activity.…”
Section: Conclusion Perspectivesmentioning
confidence: 99%